Approach to pediatric renovascular hypertension - Yeon Hee Lee; Heeyeon Cho (Childhood Kidney Diseases)
Renovascular hypertension (RVH) is an important cause of hypertension in children, but it can be cured if the cause is removed in some cases. Therefore, early diagnosis and appropriate treatment are the goals of pediatricians’ care. The cause of renal artery stenosis differs in prevalence by country. Recently, the importance of diagnosing RVH as a genetic syndrome increased. This paper reviews the current literature on the diagnosis and treatment of RVH in children.